DESKRIPSI FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN COMPUTER VISION SYNDROME (CVS) (Studi pada Karyawan Universitas Siliwangi) - Yuldan Faturrahman; Anto Purwanto (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
CVS is a complex work-related eye and vision disorder experienced as a result of computer users' use of computers. CVS is influenced by individual factors, work environment factors, and computer factors which are felt to reduce daily work productivity. The purpose of this study was to determine the factors associated with CVS complaints. This research is a descriptive study with a cross sectional approach. A sample of 75 people was taken in total sampling with the criteria of respondents aged 45 years. The results showed that the main complaints of CVS were strained or tired eyes, dry and irritated eyes, blurred vision, and headaches. Eye strain or fatigue is a type of complaint that many respondents feel. Female respondents are more at risk of complaining of CVS than male respondents. Respondents who have worked 3 years, worked for 4 hours a day are more at risk of complaining about CVS. Respondents with monitor displays of bright colored characters and dark colored backgrounds are risk factors for complaining of CVS. Respondents who have a distance of vision 50 cm are more at risk of complaining of CVS compared to respondents who have a distance of vision ≥ 50 cm. Respondents with the position of the top of the monitor against horizontal eye level that is not parallel are more at risk of experiencing CVS than those with an aligned position. Most of the respondents' workspaces have low lighting levels ( 300 lux) which is a risk factor for complaining of CVS. It is recommended that respondents pay attention to the conditions and situations when working with computers, especially improving lighting and sitting in an parallel position